2001
DOI: 10.1007/s005920170012
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic volume in type 1 und type 2 diabetes mellitus

Abstract: We measured pancreatic volume (PV) using helical computed tomography (CT) in 26 patients with type 1 diabetes mellitus (DM), 29 patients with type 2 DM, and 22 healthy individuals. We also evaluated the relationship between PV and the body surface area (BSA), established the pancreatic volume index (PVI) by dividing PV by BSA to correct PV for the body build, and examined its relationships with the duration of illness, serum C-peptide immunoreactivity level (CPR), and serum immunoreactive trypsin level (IRT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
88
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 29 publications
18
88
2
Order By: Relevance
“…Although the pancreas appeared altered on these images with large degrees of fatty infiltration, there was no difference in the overall size of the pancreas between the patients and healthy volunteers. This observation is consistent with that of Goda et al (13), who found a significantly lower pancreatic volume for patients with type 1 diabetes but no difference in the pancreas volume of patients with type 2 diabetes compared with healthy controls as measured from computed tomography (CT) images. Despite the differences in appearance and baseline T 1 value there were no significant differences in functional kinetic parameters between the normal volunteers and the patients.…”
Section: Discussionsupporting
confidence: 92%
“…Although the pancreas appeared altered on these images with large degrees of fatty infiltration, there was no difference in the overall size of the pancreas between the patients and healthy volunteers. This observation is consistent with that of Goda et al (13), who found a significantly lower pancreatic volume for patients with type 1 diabetes but no difference in the pancreas volume of patients with type 2 diabetes compared with healthy controls as measured from computed tomography (CT) images. Despite the differences in appearance and baseline T 1 value there were no significant differences in functional kinetic parameters between the normal volunteers and the patients.…”
Section: Discussionsupporting
confidence: 92%
“…While our primary focus was on indicators of vascular integrity and leukocyte infiltration, we also measured pancreas volume, given that pancreatic atrophy is a characteristic observation in long-standing T1D, as evidenced by examination of pancreas volume at autopsy, by ultrasound, by CT, or via MRI (10)(11)(12)(13). To control for the influences of body build on pancreatic volume, we calculated a pancreatic volume index (PVI) by dividing the pancreatic volume by body-surface area (12,14).…”
Section: Resultsmentioning
confidence: 99%
“…To control for the influences of body build on pancreatic volume, we calculated a pancreatic volume index (PVI) by dividing the pancreatic volume by body-surface area (12,14). Mean PVI of the patients was 31% less than that of the controls ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…All of the other subjects were prepubertal. Because pancreatic size is influenced by the body surface area, we also calculated the pancreatic volume index, where we divided the estimated pancreatic volume by the body surface area (8).…”
Section: Methodsmentioning
confidence: 99%
“…␤-Cells, which are central in the development of diabetes, constitute the major part of the islets (1). There are reports in diabetic subjects of pathological changes involving not only the islets but the entire pancreatic gland, such as pancreatic volume reduction (2)(3)(4)(5)(6)(7)(8) and lipomatosis (fatty infiltration) of the pancreas (9,10). The lipomatosis reported in autopsy studies has been described as patchy intralobular or perilobular areas of fat replacement of pancreatic parenchyma (9,10).…”
mentioning
confidence: 99%